Letters from Iwo Jima [videorecording (DVD)] - Yamashita, Iris; Haggis, Paul; Watanabe, Ken, 1959-; Ninomiya, Kazunari, 1983-; Ihara, Tsuyoshi; Kase, Ryō, 1974-; Nakamura, Shidō; Stern, Tom, 1946-; Cox, Joel; Roach, Gary D.; Eastwood, Kyle; Stevens, Michael; et al. (Clint Eastwood collection (DVD videodiscs), 2010)
Sixty-two years ago, U.S. and Japanese armies met on Iwo Jima. Decades later, hundreds of letters are unearthed from that stark island's soil, giving faces and voices to the men who fought there and more. Includes several bonus documentaries.